2016
DOI: 10.1186/s13071-016-1524-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of golden jackals (Canis aureus) as natural reservoirs of Dirofilaria spp. in Romania

Abstract: BackgroundDirofilaria immitis and Dirofilaria repens are mosquito-transmitted zoonotic nematodes, causing heartworm disease and skin lesions, respectively, in carnivores. In Europe, the domestic dog is apparently the main definitive host, but patent infections occur also in other species of carnivores. The rapid spread of the golden jackals (Canis aureus) throughout Europe opens a question of involvement of this species in the sylvatic cycle of pathogens in the colonised territories, including Dirofilaria spp.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…The importance of the presence of H. longipennis resides in its vectorial capacity, so far clearly demonstrated only for the filarial nematode A. dracunculoides (Nelson, 1963). Although the presence of A. dracunculoides in central and eastern Europe has not yet been reported despite systematic surveillance in both domestic and wild carnivores (Ionicȃ et al, 2015(Ionicȃ et al, , 2016(Ionicȃ et al, , 2017a(Ionicȃ et al, , 2017b, the presence of its vectors should raise awareness. However, the louse flies (Hippoboscidae) are not the sole vectors of this parasite as ticks [Rhipicephalus sanguineus sensu lato (Ixodida: Ixodidae)] have also been incriminated (Olmeda-Garcia et al, 1993;Olmeda-Garcia & Rodriguez-Rodriguez, 1994;Mihalca et al, 2012;Dantas-Torres & Otranto, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the presence of H. longipennis resides in its vectorial capacity, so far clearly demonstrated only for the filarial nematode A. dracunculoides (Nelson, 1963). Although the presence of A. dracunculoides in central and eastern Europe has not yet been reported despite systematic surveillance in both domestic and wild carnivores (Ionicȃ et al, 2015(Ionicȃ et al, , 2016(Ionicȃ et al, , 2017a(Ionicȃ et al, , 2017b, the presence of its vectors should raise awareness. However, the louse flies (Hippoboscidae) are not the sole vectors of this parasite as ticks [Rhipicephalus sanguineus sensu lato (Ixodida: Ixodidae)] have also been incriminated (Olmeda-Garcia et al, 1993;Olmeda-Garcia & Rodriguez-Rodriguez, 1994;Mihalca et al, 2012;Dantas-Torres & Otranto, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Different studies on the parasites’ prevalence in dogs detected local infection rates between 3% and even more than 60% [ 8 – 13 ]. In addition to domestic animals, recent studies also identified D. immitis or D. repens in different wild carnivore species (golden jackals, red fox, wildcat, grey wolf, least weasel), which probably have critical roles as reservoirs maintaining the helminths in natural disease foci [ 14 , 15 ]. Nevertheless, only a few human cases have been identified in the country so far [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is considered to be non-pathogenic, contrary to D. immitis (Ramsey, 2003). The role of wildlife species, such as the golden jackal (Ionica et al, 2016), coyote in California (Sacks, 1998), the red fox in Australia (Marks and Bloomfi eld, 1998) and the fox or wolf in Europe (Morchón et al, 2012) as reservoir hosts for Dirofi laria spp. may be of signifi cant importance in maintaining or spreading the parasite.…”
Section: Discussionmentioning
confidence: 99%